"Investigation on Zoonotic Cutaneous Leishm- aniasis, Southern Iran " - Y Rassi; E Javadian; M Jalali; MH Motazedian; H Vatndoost (Tehran University of Medical Sciences, 2004)
Since occurrence of an epidemic of cutaneous leishmaniasis with high incidence of disease (8.9/1000) in Arsanjan county, Fars province, southern Iran, an attempt was made to investigate an epidemiological study during 2001-2002. Symptomatic investigation among 270 schoolchildren over one year of study revealed that 11.9% of population had active lesion with 28.1% scar rate. Parallel study showed that among 7968 people which comprise 1572 households, 6.18% were positive for scars and 1.2% for ulcer. In our study three species of rodents, including Meriones libycus (71%), Cricetulus migratorius (22%) and Microtus arvalis (6%) were captured. By employing Nested-PCR technique, 6.8% (4 of 56) of M.libycus were found infected with Leishmania major. About 83% of indoor collected sandflies comprised, Phlebotomus papatasi. From its density it can be concluded that this species plays an important role in leishmania transmission in the area. The seasonal activity of the sandflies starts at early April and ended in early November.